2012
DOI: 10.1108/03074351211201415
|View full text |Cite
|
Sign up to set email alerts
|

REIT performance and market timing ability

Abstract: PurposeThe purpose of this paper is to study performance and market timing ability of equity real estate investment trusts (REITs).Design/methodology/approachThe authors use classical regression‐based framework and their multi‐index, multifactor, and conditional extensions to jointly detect asset selectivity and market timing ability of equity REITs and their subcategories. These results are then validated by a nonparametric test.FindingsIt is found that equity REITs in aggregate have some housing market timin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Several studies also support Jegadeesh and Titman's (1993) momentum factor as being significant in explaining REIT returns (e.g. Chui et al, 2003a,b;Hung & Glascock, 2008Derwall et al, 2009;Zhou & Ziobrowski, 2009;Buttimer et al, 2012). According to Chui et al (2003b), who analysed the performance of U.S. REITs between 1984 and 2000, the REIT momentum effect is even stronger than momentum effects encountered in other US industries.…”
Section: Reits and The Efficient Market Hypothesismentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies also support Jegadeesh and Titman's (1993) momentum factor as being significant in explaining REIT returns (e.g. Chui et al, 2003a,b;Hung & Glascock, 2008Derwall et al, 2009;Zhou & Ziobrowski, 2009;Buttimer et al, 2012). According to Chui et al (2003b), who analysed the performance of U.S. REITs between 1984 and 2000, the REIT momentum effect is even stronger than momentum effects encountered in other US industries.…”
Section: Reits and The Efficient Market Hypothesismentioning
confidence: 95%
“…Several studies also support Jegadeesh and Titman's () momentum factor as being significant in explaining REIT returns (e.g. Chui et al ., ,; Hung & Glascock, , ; Derwall et al ., ; Zhou & Ziobrowski, ; Buttimer et al ., ). According to Chui et al .…”
Section: Reits and The Efficient Market Hypothesismentioning
confidence: 97%
“…Weinbaum (2009) similarly find that the performance of lodging REITs do not measure up to the broader market, except with the ideal market timing of investment. Buttimer et al (2012) find that hospitality REITs have the lowest performance and highest volatility among REIT portfolios. On the positive side, Howton et al (2012) found that earlier studies did not fully consider property-level performance and suggest that property-level bottom line performance of REIT owned lodging properties is better than privately owned.…”
Section: Hospitality Reitmentioning
confidence: 86%
“…Kon, 1983; Chang and Lewellen, 1984; Henriksson, 1984; Ferson and Schadt, 1996; Cuthbertson et al , 2010; Mansor and Bhatti, 2014; Panda et al , 2015; Unal and Tan, 2015; Yi et al , 2018) find weak to no evidence of market timing in various markets; while others (e.g. Treynor and Mazuy, 1966; Kon and Jen, 1978; Lee and Rahman, 1990; Bello and Janjigian, 1997; Bollen and Busse, 2001; Comer, 2006; Glassman and Riddick, 2006; Jiang et al , 2007; Buttimer et al , 2012; Glabadanidis, 2014; Vidal et al , 2015; Liao et al , 2017; Andreu et al , 2018) suggest market timing abilities exist for some types of funds after controlling for factors such as liquidity, industry and portfolio.…”
Section: Introductionmentioning
confidence: 99%